ANALISIS DETERMINAN KESESUAIAN PENERAPAN PERATURAN KOMISI PEMILU RI NO. 5 TAHUN 2017 TENTANG DANA KAMPANYE PESERTA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR, BUPATI DAN WAKIL BUPATI, DAN/ATAU WALIKOTA DAN WAKIL WALIKOTA - Budi Rofelawaty; Abdul Kadir (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2018)
In the implementarion of the simultaneously post election in 2018, the Election Commission of Republic Indonesian issued regulation No.5/2017 concerning compaign funds for the participants of the Governor an Deputy Governon, regent and Deputy Regent, and/or Mayor and deputy Mayor. This research is directed at the determinants of the compliance with the implementation of the Election Commission regulation, both by candidate pairs  and by the political parties, whichs aims to find out what factors influence the implementaion of that KPU RI regulation.         The assessment process is carried out objectively, systematically, rationally, which is supported by empirical facts in order to find the truth, for the the purpose of developing science, especially regional finance, which is related to compaign funds. The research technique was carried out with descriptive fenomenology, with the location of the study being the election commission located in 11 districts and 2 municipalities in South Kalimantan province. The descriptive fenomenology approach was used by researcher to explore the phnomenon because the participants wanted to know about it (as many as 10 key person as related informants) and the researchers acted as instrumentes in teh ddata collection process.          The results of the study indicate that there are several things that have the potential to be determinants of the suitability of the implementation of The RI Election Commision regulation No.5/2017 are the electoral system and compaign finance management, the existence of a high-cost compaign process, the content of ele toral policies and the context of policy implementation (in relation of the level human resources competence, the availability of adewuate human resources, the power of actors in influencing the effectiveness for political elite).